(untitled) (Development Service Industry Management, 2024)
The operation of domestic light industry enterprises during the military aggression by the Russian Federation has led to radical transformations in approaches to ensuring their economic security. The nature and scale of threats extend beyond damage to their economic systems, posing risks to their physical existence due to missile strikes. Notably, since the beginning of the full-scale invasion, Ukraine’s light industry has faced significant economic shocks and losses caused by the destruction of production facilities, disruptions to international supply chains, raw material shortages, and the loss of skilled personnel. The goal of this research is to establish theoretical foundations and develop practical recommendations for the functioning of a mechanism to ensure the economic security of light industry enterprises through the use of modern marketing tools. These tools aim to enhance their competitiveness and resilience under conditions of economic instability. The existence of risk factors for domestic light industry enterprises fundamentally redefines the role and importance of the marketing component in the economic security system. This includes setting its goals and objectives, procedures for risk assessment and identification, and designing a model mechanism with a clear representation of interconnections between all elements of the economic security system. It also involves creating a list of tools and specific methods to achieve set objectives. Simultaneously, the formation of this mechanism must account for the integration of the marketing component into the economic security system of light industry enterprises. This is essential for balancing risk and security factors, which is one of the primary tasks of any economic security system, especially in the context of modern challenges and threats faced by Ukraine’s light industry enterprises. Taking this into account, the authors propose a structural-logical model of a mechanism to ensure the economic security of light industry enterprises based on the use of marketing tools. A significant place in this mechanism is occupied by marketing tools for evaluating the economic security of an enterprise, including early warning systems, marketing research, risk mapping, supply chain analysis, demand elasticity analysis, reputation monitoring, and SWOT, PEST, and SNW analyses. Thus, the proposed mechanism for ensuring the economic security of light industry enterprises through the use of marketing tools considers existing risk factors, the contemporary aspects of enterprise operation, the peculiarities of their external environment, and marketing activities. It emphasizes the application of marketing tools to assess the level of danger, methods to ensure economic security, and strategies to enhance resilience, competitiveness, and development. This is achieved by mitigating risks, minimizing threats, and effectively using marketing tools to adapt to changes in market conditions.